(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study focuses on the synthesis, characterization, and application of a manganese dioxide (MnO₂)/biochar (BC) composite for the removal of contaminants from water. The MnO₂/BC composite was synthesized through a co-precipitation method, where biochar derived from [insert biomass source] was used as a supporting matrix for MnO₂ nanoparticles. The composite was characterized using techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR) to confirm the successful synthesis and to analyze its structural and surface properties. The removal efficiency of the composite was evaluated for various water contaminants, including heavy metals and organic pollutants. The results demonstrated that the MnO₂/BC composite exhibits high adsorption capacity, rapid kinetics, and good reusability, making it a promising material for water purification applications. The underlying mechanisms of adsorption and the influence of operational parameters such as pH, contact time, and initial concentration were also investigated to optimize the removal process. This study provides a comprehensive understanding of the potential of MnO₂/BC composites in environmental remediation, particularly in the treatment of contaminated water.